Dinamika Identitas Kewarganegaraan Dalam Konteks Globalisasi: Studi Kasus Di Era Digital - Tita Ester; Bintang Auliya Tyananda; Ryan Dwi Prayoga; Dela Amelia; Eni Lutviana Fadila; Naifa Adelia (International Forum of Researchers and Lecturers, 2024)
Globalization is a modern development that has influenced the emergence of various possibilities to change the world. The impact of globalization has the potential to make the world more open and remove the barriers that make us need each other. This research aims to reveal the dynamics of citizenship identity in the context of globalization. Over time, the term